EKSPLORASI MOTIF RENDO BANGKU KOTO GADANG SUMATERA BARAT PADA PRODUK FASHION - Ranelis, Ranelis; Rahmad, Washinton; Kendall, Malik (Narada : Jurnal Desain dan Seni, 2022)
Article with the title "Exploration of the Rendo Bangku Koto Gadang motif in West Sumatra in Fashion Products" aims to increase the number of motifs and products from the rendo Bangku Koto Gadang craft in West Sumatra into quality products and have their own characteristics. Koto Gadang Village. The rendo bench product which was originally used for decoration on the edge of the Koto Gadang women's scarf, is now being developed in the form of diversification of form and function by applying Koto Gadang rendo to women's clothing and men's clothing. The method used in this research is the experimental method. By way of exploration and design. Based on the results of exploration and design, we have been able to produce designs for rendo bench motifs, clothing designs for women and clothing designs for men.